Effect of genetic and non-genetic factors on semen production performance of Karan Fries and Tharparkar breeding bulls - PANMEI, A; GUPTA, A K; SHIVAHRE, P R; SINGH, AVTAR; DASH, S K; BHAKAT, M (The Indian Journal of Animal Sciences, 2016)
The present study was conducted at Artificial Breeding Research Centre, to ascertain the influence of genetic (3 genetic groups of Holstein Friesian and Tharparkar crosses and pure Tharparkar) and non genetic (Periods i.e.,1997– 2000, 2001–2004, 2005–2008 and 2009–2012; seasons i.e., winter, summer, autumn and rainy; age group i.e., <2 yrs, >2–2.5 yrs, >2.5–3 yrs and >3 yrs) factors on semen production performance of Karan Fries (KF) and TP breeding bulls. Overall percent of males reserved for breeding was 16.67% in KF and 22.73% in TP. Out of males reserved for breeding, 58.97% KF and 20% TP males produced semen. Only 64.9% produced freezable semen in KF bulls whereas in TP bulls, all males which donated semen produced freezable quality semen. Periods of birth showed significant effect on % age at first successful collection (AFSC) and (P<0.05) % age at first successful freezing (AFSF) (based on AFSC) in KF, wherein genetic groups revealed significant influence on % AFSC and % AFSF (on the basis of >18 months of age). For both KF and TP, overall least square means of AFSC, AFSF, ALSF (age at last successful freezing), ALSC (age at last successful collection), SPP (semen production period), FSPP (freezable semen production period) and AD (age at disposal) were 879.21, 1077.65, 1659.87, 1425.53, 831.82, 775.44 and 1329.38 days, respectively. Effect of period of birth was significant for all the traits except AFSC. Season of birth had no significant effect on all the traits while genetic groups and age at disposal have significant effect on AFSC and AFSF, respectively.